Gap Analysis of the Environmental Management System Performance of PT. XXX to ISO 14001:2015 Standard - Adri Efendi; Sodikin Sodikin; Prabawa Eka Soesanta (Jurnal Indonesia Sosial Teknologi, 2024)
PT. XXX is one of the oil and gas exploration companies in Indonesia operating in the Rokan Block of the Riau Province. To maintain the level of petroleum production in operation, PT. XXX adds oil and gas wells, improves, and improves operation reliability through upgrading several existing facilities; seen from the environmental setting at the current operational location activity has an impact on environmental components. To mitigate it, PT. XXX has developed an Environmental Management System (EMS) according to the international standard ISO 14001:2015. This quantitative descriptive research aims to determine the gap in QMS performance implemented by companies with ISO 14001: 2015 standards using seven clauses: Self-Assessment Checklist Internal Audit ISO 14001: 2015 GEMI 2015. To find out the Company's SML gap score with ISO 14001: 2015 standard is determined by the Gap Analysis method. The gap results from the 7 (seven) clauses analyzed to show the readiness score of SML PT. XXX to implement ISO 14001:2015 Standard is 98.83% refers to range gap analysis if the score range of 75% - 100% indicates PT. XXX is ready to complement EMS ISO 14001:2015 and carry out certification. The gap score between the Company's Environmental Management System (EMS) that is being implemented and the ISO 14001:2015 standard is 1.17%. The gap in clauses that have not met the requirements of SML ISO 14001: 2015 is Clause Support, which scores 95%, and Clause Performance Evaluation, which scores 96%.